KESESUAIAN RPP DENGAN PELAKSANAAN PEMBELAJARAN GURU BIOLOGI SMP KELAS VIII SE-KECAMATAN KEPENUHAN HULU TAHUN PEMBELAJARAN 2015/2016 - sari, elmida (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
The purpose of this study is to determine the appropriation of RPP with biology teacherâs implementation of learning process on Junior High School in Kepenuhan Hulu. The study was carried out from March to August. The method used in this research is descriptive. Population and sample used was Junior High School Biology teacher in Kepenuhan Hulu. Based on the result of analysis the highest value of IPKG-1 was 3,18% with good category while the lowest one was 2,65% with good category. The highest value of IPKG-2 was 3,26% with good category and the lowest one was 2,29% with good category. The conclusion of this study that the appropriation of RPP with biology teacherâs implementation of learning process was 2,82% with good category.